(untitled) (College of Basic Education Research Journal, 2026)
This study aims to analyze the philosophy of Khilafah (vicegerency) in Islamic education as a comprehensive epistemological and value-based framework, and to explore its relationship with the concept of sustainable education in its cognitive, skill-based, affective, and behavioral dimensions. The central hypothesis of the research asserts that the philosophy of Khilafah provides a moral and intellectual foundation capable of achieving balance between spiritual-ethical values and the requirements of sustainable human developmentin contemporary societies. The study adopted a descriptive-analytical methodology analyzing Qur’anic and Prophetic texts related to stewardship, as well as reviewing modern educational literature on sustainable development and its alignment with Islamic objectives (Maqasid al-Shariah), such as the preservation of life, intellect, environment, and civilization. A practical educational model was also implemented to assess the influence of Khilafah-based values on learners’ cognitive and affective growth. Findings revealed that the philosophy of Khilafah represents a core pillar for building sustainable education, as it fosters a deep sense of personal and collective responsibility toward oneself, society, and the environment. Integrating stewardship values within educational processes significantly enhanced students’ overall learning outcomes particularly in critical thinking, environmental awareness, ethical practice, and responsible teamwork. Moreover, the study confirmed that applying Khilafah-oriented educational activities transforms learning from mere knowledge transmission into a process of moral and creative human development, equipping students to address global social and environmental challenges through an Islamic ethical lens. The study concludes that linking Khilafah philosophy with sustainable education offers a holistic pedagogical model for achieving the UN’s Sustainable Development Goals (SDGs) within an Islamic moral framework. Accordingly, the study recommends: 1. Integrating the philosophy of Khilafah into school curricula and environmental education. 2. Training teachers to apply stewardship-based pedagogies in classroom activities. 3. Developing assessment tools to measure value-based and behavioral sustainability outcomes. Encouraging comparative field studies on the impact of Islamic value-centered education on sustainable community building.